PENGARUH MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN MEDIA INFOGRAFIS TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS X SMA NEGERI 1 LEMBAH MELINTANG - Ilmi Rahma Dianti; Indriani Nisja; Samsiarni Samsiarni (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2026)
This study aims to examine the effect of the Project-Based Learning (PjBL) model assisted by infographic media on the observation report text writing skills of Grade X students at SMA Negeri 1 Lembah Melintang. This study employed a quantitative approach with an experimental method and a One-Group Pretest-Posttest Design. The population consisted of 337 students, while the sample comprised 34 students from Grade X E10 selected using purposive sampling. Data were collected through a performance-based test requiring students to write observation report texts, which were assessed based on textual structure and linguistic features. The data were analyzed descriptively and inferentially using the Shapiro-Wilk normality test and a Paired Samples t-test. The results showed that the students’ mean score increased from 83.09 in the pretest to 94.00 in the posttest, representing an increase of 10.91 points. The Paired Samples t-test yielded t = -7.111, df = 33, and p < 0.001, indicating that H₀ was rejected and H₁ was accepted. Thus, the PjBL model assisted by infographic media had a significant effect on students’ observation report text writing skills. Improvements were also observed in the indicators of general statement, description of parts, description of benefits, adjectives, technical terms, and concrete words. These findings indicate that integrating PjBL with infographic media can help students organize observational findings and develop them into texts that are more systematic and consistent with the characteristics of observation report texts.